ChemInform Abstract: Phase‐Transfer‐Catalyzed Synthesis of Pyrroloindolines and Pyridoindolines by a Hydrogen‐Bond‐Assisted Isocyanide Cyclization Cascade. Issue 35 (2nd September 2014) - Knipe, Peter C.; Gredicak, Matija; Cernijenko, Artiom; Paton, Robert S.; Smith, Martin D.
Abstract The entitled cascade reaction proceeds in the presence of a quaternary ammonium catalyst and base generating functionalized products with an all‐carbon quaternary stereocenter.